Interaction of Platelet Membrane Receptors with von Willebrand Factor, Ristocetin, and the Fc Region of Immunoglobulin G - Moore, Anne (1978)
The agglutination of human platelets by ristocetin and von Willebrand factor was inhibited by aggregated immunoglobulin (Ig)G and by Fc fragments of IgG, but not by Fab, F(ab′)(2) or pFc fragments of IgG. Because this inhibition occurred with formalin-fixed platelets as well as with normal platelets, a generalized aggregation of fluid membrane components by Fc fragments was not responsible for this inhibition of ristocetin and von Willebrand factor-induced agglutination. Reciprocal inhibition of platelet Fc receptors was produced by prior incubation of platelets with von Willebrand factor and ristocetin. Sucrose density gradient ultracentrifugation studies demonstrated that aggregated IgG did not form fluid-phase complexes with von Willebrand factor and ristocetin. Furthermore, passage of von Willebrand factor and ristocetin through a column of immobilized heat-aggregated IgG did not alter platelet agglutinating activity which indicates that aggregated IgG did not inactivate von Willebrand factor or ristocetin. Thus, it was likely that the IgG-mediated interference with platelet agglutination by ristocetin and von Willebrand factor did not occur in the fluid phase but at the platelet surface. These studies suggest that the platelet membrane Fc receptor may be either a part of, or sterically related to, the membrane glycoprotein I complex that interacts with von Willebrand factor, and that occupation of one of these surface components blocks the availability of the other.